'Defunding the police': A consideration of the implications for the police role in mental health work. (June 2023) - Cummins, Ian
This paper examines the role of the police in mental health work. It explores whether the calls to 'defund the police' can be the basis for fundamental reforms of mental health services and the police role. The paper outlines the roots of the calls to ' defund the police' situating the perspective in the wider Black Lives Matter movement (BLM). The wider BLM movement seeks to overturn long standing racial and social injustices, including the disproportionate use of force against black citizens and racial biases within the Criminal Justice System. It goes further in that BLM calls for a shift in funding from policing towards an investment in welfare and community services. These calls are captured in the phrase 'defund the police'. These calls have highlighted the police role in mental health, particularly, the police response to citizens in mental health crisis. The paper examines the police role in mental health work, highlighting the historic impact of policies of deinstutionalisation and more recently austerity and welfare retrenchment. In calling for this policy shift, campaigners have highlighted the need to significant investment in mental health services. The police role in mental health services increased because of the failings of community care (Cummins, 2020a ). Police officers have increasingly become first responders in mental health crises. The paper, focusing on England and Wales, uses 'defund the police' perspective as a lens to examine long standing areas of concern. Police involvement in mental health emergencies is inevitably stigmatizing. There are also concerns from the police. This is an area of police demand that has grown of austerity and the wider retrenchment in public services. Police officers often feel that they lack the skills and knowledge required to undertake their role in mental health work. In addition, there is frustration generated by poor interprofessional working. Police officers on an organizational and individual level feel that they are often left ' picking up the pieces ' . There is a wide recognition that mental health services are failing to provide appropriate responses to those in crisis (Wessley, 2018 ). As well as being an issue of human rights and social justice, these failures place vulnerable people at increased risk. All aspects of police work involve contact with people experiencing mental health problems. People with mental health problems are first and foremost human beings who should be treated with dignity and respect. They are also citizens, family members, carers and work colleagues. Having acknowledged that core value perspective, if we accept that police officers will be involved in mental health work, we should seek to limit their role as far as is possible. The paper concludes that it is likely that there will be always be some form of police involvement in mental health–related work. However, there is a need to limit this as far as possible.